Intimacy and Abundance: Textile Relics, the Veronica, and Christian Devotion in the Aftermath of the Fourth Crusade - Lester, Anne Elisabeth (Material religion, 2018)
During the early thirteenth century crusaders carried or sent dozens of textile relics from the treasuries of the Levant and Byzantium to the West. As these objects were integrated into the devotional life of western Europe, they collapsed the perceptions of temporal and spatial distance between medieval Europe and the world of the Apostles. Taking as a case study Pope Innocent III's renewed veneration of the sudarium, or Veil of Veronica, the article investigates the inherent and potent material qualities of cloth as a medium of holiness. The abundance of cloth relics coming into the West underlined the power of the divine presence. Whereas the intimacy promised by cloth-material made, touched, worn, soiled, and carried by the hands of others-brought the Holy Land and the physical realities of Christ's life and Passion into the heart of western Europe. Cloth evoked the bodies of its bearers and makers, referencing Christ, Mary, the Apostles, but also those who carried or sent such relics to the West, for example, crusaders who did not return to their kin. The intimacies of cloth, moreover, contributed to the generation of an abundance of other, new, and imitative relics over the course of the medieval period.